Impact of child marriage on nutritional status of women from suburban and urban areas of West Bengal - Das, Tanima; Adhikari, Anup (International Journal Of Community Medicine And Public Health, 2020)
Background: Child marriage is a substantial barrier to social and economic development of a country and a primary concern for women’s health. In West Bengal, the practice of early marriage is still running especially in Muslim community. The present study was aimed to find out the impact of child marriage on nutritional status of mother in terms of BMI. Methods: 117 Muslim women from both North and South 24 Parganas districts of West Bengal were studied. All of them were from economically lower middle class group. Height, weight, age, age at marriage, age at 1st child birth, number of children, family income and other information were recorded. Results: During the study, the average age of 117 Muslim women was 28.4±3.7 years with a range of 21-41. Average age was 18.0±1.9 years when the Muslim women got married. 83.6% women who got married in childhood were in underweight category of which 15.8% were in severe thinness category. But 86.9% women who got married after 18 year were in normal weight category. Only 5.3% women of this group were in underweight category. Conclusions: Thinness of the mother was might be due to marriage before 18 year. Thus from the above study it could be concluded that child marriage had a negative impact on mother’s nutritional status in terms of BMI.